2017
DOI: 10.3389/fpls.2017.01136
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Breeding for Ascochyta Blight Resistance in Lentil: Current Progress and Future Directions

Abstract: Lentil (Lens culinaris Medik.) is a diploid (2n = 2x = 14), self-pollinating, cool-season, grain legume that is cultivated worldwide and is highly valuable due to its high protein content. However, lentil production is constrained by many factors including biotic stresses, majority of which are fungal diseases such as ascochyta blight (AB), fusarium wilt, rust, stemphylium blight, anthracnose, and botrytis gray mold. Among various diseases, AB is a major -problem in many lentil-producing countries and can sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 81 publications
(150 reference statements)
0
21
0
Order By: Relevance
“…Several genetic linkage maps have previously been used to identify QTLs for Ascochyta blight resistance in lentil (reviewed by Rodda et al [89]), with magnitudes varying from 3% to 89% of the phenotypic variance evidenced. Common QTL locations between different studies are difficult to establish because of the differing nomenclature for linkage groups and the lack of common marker loci between the genetic maps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genetic linkage maps have previously been used to identify QTLs for Ascochyta blight resistance in lentil (reviewed by Rodda et al [89]), with magnitudes varying from 3% to 89% of the phenotypic variance evidenced. Common QTL locations between different studies are difficult to establish because of the differing nomenclature for linkage groups and the lack of common marker loci between the genetic maps.…”
Section: Discussionmentioning
confidence: 99%
“…Common QTL locations between different studies are difficult to establish because of the differing nomenclature for linkage groups and the lack of common marker loci between the genetic maps. In spite of that, the QTL named AB_NF1 on LG6 in the study of Sudheesh et al [67] is comparable in position to QTL5 on LG1 of Rubeena et al [85] and QTL1 on LG1 of Gupta et al [49], based on a common SSR locus location [89]. The AB_NF1 QTL accounted for 7% of the phenotypic variation in an F 6 RIL population from a cross of Indianhead x Northfield, being Northfield (ILL5588) a common parent in the majority of the studies published.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both Indianhead and Northfield (syn. ILL5588, Nei's coefficient value 0.69194), known to be resistant to Ascochyta Blight (Rodda et al, 2017), have been crossed to each other to produce improved levels of disease resistance in the breeding germplasm (Rodda et al, 2017). The information generated in the current study provides a database for breeders to select Lens accessions for future crossing strategies in order to introgress novel alleles.…”
Section: Assessment Of Genetic Diversity and Population Structure In mentioning
confidence: 99%
“…Using RIL populations, QTLs for stemphylium blight and rust resistance (Saha, Sarker, Chen, Vandemark, & Muehlbauer, 2010a, 2010b) and seedling and pod stage ascochyta blight resistance (each of three QTLs, accounted for 34% and 61% of the total estimated phenotypic variation (Gupta, Taylor, et al, 2012) were identified. Nevertheless, identified flanking markers have potential to be used in MAS especially for disease-resistance genes with single gene inheritance or codominance (Chowdhury, Andrahennadi, Slinkard, & Vandenberg, 2001;Eujayl et al, 1998;Ford, Pang, & Taylor, 1999;Kaur et al, 2014;Rodda et al, 2017;Rubena, Taylor, Ades, & Ford, 2006;Tullu et al, 2003). However, validation of these linked markers would remain important challenge for the success of adoption of such markers in lentil improvement programme.…”
Section: Qtl Mapping and Mas In Breeding Programmesmentioning
confidence: 99%
“…These AB-resistant markers were evaluated on a diverse lentil panel, which had nearly 86% accuracy for phenotypic response to be potentially adopted in lentil breeding programmes. Ascochyta blight-resistant genes have been identified through lentil genomics and integrated genetic linkage map, EST libraries and draft genome sequences have been generated (Rodda et al, 2017). Among few attempts to dissect genes of interest from wild genotypes using mapping and QTL analysis, a linkage map of 94 RILs from a cross between two L. ervoides genotypes has been developed (Bhadauria, Ramsay, Bett, & Banniza, 2017 34 countries with a wide range of variation for zinc (Zn) and iron (Fe) concentration in seeds were used, and two SNP markers tightly linked to Fe and one linked to Zn concentration were identified using marker-trait association analysis (Khazaei et al, 2017).…”
Section: Qtl Mapping and Mas In Breeding Programmesmentioning
confidence: 99%